Environmental Biotechnology and Cleaner Bioprocesses - Olguin, Eugenia J;Ed. Sanchez, Gloria;Ed (Taylor & Francis, 2000)
"Environmental biotechnologies are increasingly being viewed as a major weapon against environmental damage. Cleaner production is part of this strategy and yet there is still widespread ignorance about this emerging technology." "Environmental Biotechnology and Cleaner Bioprocesses provides this information at various levels, from introductory to advanced. The first section covers the development of cleaner bioprocesses within the framework of sustainable development. Aspects of environmental policy for small and medium businesses are then discussed using case studies to illustrate principles. The second section covers the recycling and treatment of organic waste, including the use of aquatic plants and microalgae for wastewater treatment and recovery of nutrients. Section three covers bioremediation technologies and finally, section four is dedicated to emerging cleaner bioprocesses and environmentally sound products." "Students and professionals interested in environmental biotechnology and cleaner production will find the background information and detail they require in this one source."--Jacket.